Zadłużenie i wynik operacyjny gmin w świetle uwarunkowań prawnych i samorządowych wydatków inwestycyjnych - Zawora, Jolanta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2013)
The debt of the polish municipalities in 2007–2011 grew steadily. The especially high increase in debt of the local government sector has occurred after 2008. Among the different types of local governments municipalities and cities with county rights generated local government debt by most. The especially high increase in debt has occurred in 2009–2011. With the increase in the debt of municipalities in the period 2007–2010, the share of investment expenditures in total expenditure was increasing too. However performed municipal investments were stopped in 2011. The reasons for reducing investment expenditures by local governments are associated with the deterioration of macroeconomic conditions and changes in the legal conditions of functioning of municipalities.